2015
DOI: 10.1002/jbmr.2513
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol, a Major Non-Psychotropic Cannabis Constituent Enhances Fracture Healing and Stimulates Lysyl Hydroxylase Activity in Osteoblasts

Abstract: Cannabinoid ligands regulate bone mass, but skeletal effects of cannabis (marijuana and hashish) have not been reported. Bone fractures are highly prevalent, involving prolonged immobilization and discomfort. Here we report that the major non-psychoactive cannabis constituent, cannabidiol (CBD), enhances the biomechanical properties of healing rat mid-femoral fractures. The maximal load and work-to-failure, but not the stiffness, of femurs from rats given a mixture of CBD and D 9-tetrahydrocannabinol (THC) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 49 publications
(81 reference statements)
2
48
0
3
Order By: Relevance
“…CBD exerts beneficial effects on bone formation and fracture healing (443) and reduces bone resorption in vivo in mice. Antagonism of GPR55, which suppresses osteoclast formation but stimulates osteoclast function, seems to underlie CBD negative effects on osteoclast function (914).…”
Section: Bone Formation and Fracture Healingmentioning
confidence: 99%
“…CBD exerts beneficial effects on bone formation and fracture healing (443) and reduces bone resorption in vivo in mice. Antagonism of GPR55, which suppresses osteoclast formation but stimulates osteoclast function, seems to underlie CBD negative effects on osteoclast function (914).…”
Section: Bone Formation and Fracture Healingmentioning
confidence: 99%
“…Thus, in another investigation inhibition of the CB 1 receptor was found to be associated with resistance to ovariectomy-induced bone loss via inhibition osteoclast differentiation [ 8 ]. Finally, other studies reported enhanced bone loss in wild-type compared with CB 2 knockout mice [ 53 ] and found CBD to gain fracture healing [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small number of preclinical studies have investigated the effects of CBD on bone structure and function [103,112,135]. While most have used animal models that are limited in their direct relevance to sport and/or exercise performance (e.g.…”
Section: Bone Healthmentioning
confidence: 99%